Application of Maggot Debridement Therapy on Infected Wounds of Newborns: A Case Series in Iran - Sajjad Motallemzadeh; Tabaie, Seyed; Mirzaei, Jamal; Akbarzadeh, Kamran; Djavid, Gholamreza; Sabo, Yusuf; Yusuf, Mustapha; Malekian, Azam (Nigerian Journal of Basic and Clinical Sciences, 2026)
Neonates hospitalized in the Neonatal Intensive Care Units (NICU) are exposed to a higher risk of iatrogenic skin lesions. Maggot Debridement Therapy (MDT) in recent years has gotten more attention as a debriding, and disinfecting agent. The aim of this study was to treat infants with infected wounds and to evaluate the effectiveness and safety of MDT on in this group of patients. The study was conducted on four infants (12 to 30 days old) with infected wounds who could not withstand surgical debridement.Lucilia sericatalarvae were used along with other standard therapies. The result of this study showed that MDT is an effective biological debridement tool with a good safety margin amongst infants. It removes all the necrotic tissue and induced granulation after application. In addition, it shortens the healing time, reduced pain, and decreased the rate of antibiotic consumption thereby reducing the overall cost of management.